Spiritual Well-Being, Self-Care, and Quality of Life in Indonesian Patients with Coronary Heart Disease: A Correlational Study in a Regional Hospital of Cirebon, Indonesia - Syaripudin, Ahmad (Media Publikasi Cendekia Indonesia, 2025)
Coronary heart disease (CHD) is the leading cause of mortality globally. The quality of life of CHD patients is not only influenced by physical conditions, but also by psychological, spiritual, and self-care behaviors. Investigate the relationship between spiritual well-being and self-care with quality of life in coronary heart disease patients in the hospital. This study used a quantitative correlational design with a cross-sectional approach. A total of 93 coronary heart disease (CHD) patients receiving outpatient care at Gunung Jati Cirebon City Regional Hospital were selected through purposive sampling. The instruments used were the Spiritual Well-Being Scale (SWBS), the Self-Care of Coronary Heart Disease Inventory (SC-CHDI), and the SF-36 Health Survey to measure quality of life. Data were analyzed using Pearson correlation and multiple linear regression. There was a significant positive relationship between spiritual well-being and quality of life (r = 0.56; p < 0.001), as well as between self-care and quality of life (r = 0.64; p < 0.001). Multiple regression analysis revealed that both spiritual well-being and self-care significantly influenced quality of life (R² = 0.72; p < 0.001), indicating that these factors together explained 72% of the variance in quality of life among CHD patients. Notably, self-care emerged as the stronger predictor. These findings highlight the critical role of both spirituality and self-care in enhancing patients’ well-being. Integrating spiritual support and self-care education into nursing practice is recommended to improve the quality of life in individuals with coronary heart disease.